The Impact of Multisensory Method on Students’ Memorizing Vocabulary at Halimah Kindergarten Prenduan Sumenep - Nailan Al Adzillina; Henny Uswatun Hasanah (Institut Agama Islam Negeri Madura, 2021)
Young learners were aged 5-6 have a golden age to master a new language since they have good memorization in their brains. It is similar to the phenomenon at Halimah Kindergarten Prenduan Sumenep. 11 students had mastered their first language (Indonesian) 8 of 11 students among them cannot answer the teacher's question about English vocabulary of profession after the teacher taught learning vocabulary in the classroom. Additionally, the students are still difficult to answer the questions. Ultimately, this research measures whether kindergartens students learning vocabulary with the Multisensory Method have better-memorizing vocabulary and the significant impact of the Multisensory Method after treatment. The researcher conducted research using a quantitative approach with consist pre-experimental design. The data was obtained by observing pre-test and post-test. Likewise, documentation was used to legitimize the data. The data result found that learning vocabulary for the young learner is easier to understand if the teacher applies a multisensory method (t value: 5.164) which is higher than t table 2.23. Hence, the multisensory method is an excellent method to be applied for kindergarten in the classroom.